The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00018-023-04790-z
|View full text |Cite
|
Sign up to set email alerts
|

Darwin’s agential materials: evolutionary implications of multiscale competency in developmental biology

Abstract: A critical aspect of evolution is the layer of developmental physiology that operates between the genotype and the anatomical phenotype. While much work has addressed the evolution of developmental mechanisms and the evolvability of specific genetic architectures with emergent complexity, one aspect has not been sufficiently explored: the implications of morphogenetic problem-solving competencies for the evolutionary process itself. The cells that evolution works with are not passive components: rather, they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 298 publications
0
23
0
Order By: Relevance
“…A fascinating body of work exists around the question of how neural and non-neural problem-solving capacities evolved, and how neuro-behavioral intelligence affects evolution [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . However, we and others have previously suggested that somatic competency pre-dates neural intelligence [32][33][34] , and has a bi-directional interaction with the evolutionary and developmental process 1,3,35 . Thus, here we address the second half of the evolution-intelligence spiral: how are evolutionary processes affected by the competency of the material?…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…A fascinating body of work exists around the question of how neural and non-neural problem-solving capacities evolved, and how neuro-behavioral intelligence affects evolution [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . However, we and others have previously suggested that somatic competency pre-dates neural intelligence [32][33][34] , and has a bi-directional interaction with the evolutionary and developmental process 1,3,35 . Thus, here we address the second half of the evolution-intelligence spiral: how are evolutionary processes affected by the competency of the material?…”
Section: Introductionmentioning
confidence: 75%
“…Through a computational lens, such a competency transfer would also allow, as soon as the structural part of the genome is reliable enough, to re-purpose the system's competency to adapt to other, independent tasks, and thus may facilitate the in biology ubiquitous effect of polycomputing in related systems 123 . This all illustrates that an agential material 1,94 , or more precisely a substrate composed of competent parts, can have significant effects on the process of evolution and evolvability, especially for morphogenesis tasks. We thus conclude that, if competent parts are available, evolution prefers exploiting competency over direct encoding -if the environment requires competency at all (see discussion in section III C).…”
Section: B Direct Vs Multi-scale Encoding: Cellular Competencies Affe...mentioning
confidence: 88%
See 3 more Smart Citations